2019
DOI: 10.3389/fnins.2019.00715
|View full text |Cite
|
Sign up to set email alerts
|

Non-motor Brain Regions in Non-dominant Hemisphere Are Influential in Decoding Movement Speed

Abstract: Sensorimotor control studies have predominantly focused on how motor regions of the brain relay basic movement-related information such as position and velocity. However, motor control is often complex, involving the integration of sensory information, planning, visuomotor tracking, spatial mapping, retrieval and storage of memories, and may even be emotionally driven. This suggests that many more regions in the brain are involved beyond premotor and motor cortices. In this study, we exploited an experimental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Plastic changes taking place at this time should relate to various components of motor activity, such as integration of somato-sensory and visuospatial information into motor plans, and acquisition of new motor skills through procedural learning. This suggests that brain regions beyond the premotor and motor cortices take part in the process 89 . Notable among the cortical components of the re-organizing network is the insula, in which the existence of damage to almost half of its voxels was found to affect patients’ FMA-UL scores.…”
Section: Discussionmentioning
confidence: 99%
“…Plastic changes taking place at this time should relate to various components of motor activity, such as integration of somato-sensory and visuospatial information into motor plans, and acquisition of new motor skills through procedural learning. This suggests that brain regions beyond the premotor and motor cortices take part in the process 89 . Notable among the cortical components of the re-organizing network is the insula, in which the existence of damage to almost half of its voxels was found to affect patients’ FMA-UL scores.…”
Section: Discussionmentioning
confidence: 99%
“…Above chance gesture decoding has been demonstrated in several studies [10], [11]. Breault et al [12] decoded movement speed with a correlation of 0.38 ± 0.03, and 70% ± 3% when decoding three speed levels.…”
Section: Background -Related Workmentioning
confidence: 86%
“…Attempts to decode movement direction (Johnson et al, 2017) and path information (Breault et al, 2017) have found few modulated areas and correlations that reached statistical significance but were on the order of r =0.2. A study decoding movement speed that used a more complex classification method, least absolute shrinkage and selection operator (LASSO) linear regression, had a higher correlation of r= 0.4 on average but with a large range of correlations across subjects and a mean squared error greater than one (Breault et al, 2019). Unlike these studies, we chose to classify using a baseline without movement to quantify the extent to which the brain areas recorded by sEEG were related to movement in general and focused on individual electrode contacts instead of patient-level data.…”
Section: Discussionmentioning
confidence: 99%